2016
DOI: 10.5812/ircmj.38045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Systemic Lupus Erythematosus Disease Activity Index Scores and Subclinical Cardiac Problems

Abstract: BackgroundSystemic lupus erythematosus (SLE) is an autoimmune connective-tissue disease involving multiple organs and systems. Some evidence has demonstrated that disease activity could be associated with increased risk of organ damage.ObjectivesThe aim of this study was to determine the association between systemic lupus erythematosus Disease Activity Index (SLEDAI) scores and subclinical cardiac involvement.MethodsThis cross-sectional study was conducted on 45 SLE patients (88% female; mean age: 31.2 ± 8.2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Echocardiographic examinations have been increasingly implemented in patients with different rheumatologic diseases with the aim of evaluating cardiac functions and structures. 37 - 39 The systolic and diastolic functions of the heart have been found to be impaired in patients with AS in addition to classic aortopathies and arrhythmias. Kiris et al 13 found that their patients with AS had LV systolic asynchrony, which might lead to cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic examinations have been increasingly implemented in patients with different rheumatologic diseases with the aim of evaluating cardiac functions and structures. 37 - 39 The systolic and diastolic functions of the heart have been found to be impaired in patients with AS in addition to classic aortopathies and arrhythmias. Kiris et al 13 found that their patients with AS had LV systolic asynchrony, which might lead to cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Using this guideline in patients with RA, SPA, and SLE is complicated by the poor functional capacity of many patients prior to THA and TKA, when poor functional capacity is defined as the inability to achieve at least 4 Metabolic Equivalents (METS), achieved by light shoveling, dancing, or gardening, defining "light" as when the activity results in "only minimal perspiration and only a slight increase in breathing above normal" [69]. Moreover, patients with RA with cardiovascular disease may not have symptoms [48,70,71]. Using the classic Framingham risk equation (based on age, sex, total cholesterol level, high density lipoprotein cholesterol level, smoking history, and systolic blood pressure), patients with RA, SPA, and SLE may fall into a low risk category, leading some to add the presence of a systemic inflammatory disease such as RA, SPA, and SLE to the list of traditional cardiovascular risk factors, or to add a multiplication factor of 1.4 to the calculation of cardiac risk, recognizing that the current risk assessment tools are unreliable and underestimate cardiac risk in patients with RA, SPA, and SLE [51,[72][73][74][75][76].…”
Section: Major Acute Cardiac Eventsmentioning
confidence: 99%
“…Mirfeizi et al . [ 21 ] found that patients with higher disease severity index and longer disease duration had higher pulmonary artery pressure rates ( r = 0.34, P = 0.024) and ( r = 0.43, P = 0.004), but there was no correlation found between disease severity index or disease duration and left ventricular systolic function parameters. This may be attributed to the differences in clinical demographics, disease duration, and severity index from our study.…”
Section: Discussionmentioning
confidence: 99%